Baseline Occlusion Angiographic Appearance on Mechanical Thrombectomy Suggests Underlying Etiology and Outcome - Garcia-Bermejo, Pablo; Patro, Satya Narayana; Ahmed, Ayman Z.; Al Rumaihi, Ghaya; Akhtar, Naveed; Kamran, Sadaat; Salam, Abdul; Own, Ahmed; Saqqur, Maher; Shuaib, Ashfaq (Frontiers in Neurology, 2019)
Background: Etiology of a large vessel occlusion is relevant in the management of acute ischemic stroke patients and often difficult to determine in the acute phase. Aims: We aim to investigate whether the angiographic appearance of the occlusion is related to its etiology and outcome. Materials and Methods: Patients without cervical carotid occlusions who underwent mechanical thrombectomy in our center from April 2015 to September 2018 were studied. Demographics, clinical and radiological variables and outcome measures, including etiological classification of stroke, were collected. Underlying intracranial atherosclerosis was estimated according to the presence of stenosis after recanalization. Patients were assigned to groups based on the appearance of the occlusion observed in the first angiogram as “tapered” or “non-tapered.” Differences were searched amongst them. Results: 131 patients met inclusion criteria. 31 (23.6%) were “tapered” and 100 (76.3%) non-tapered. Tapered presented lower mean baseline NIHSS (10.3 ± 6.2 vs. 16.1 ± 7.2; p < 0.001), smaller acute infarct cores as CTP CBV ASPECTS (8.6 ± 1.6 vs. 7.2 ± 2.4; p = 0.003), higher proportion of instant re-occlusions (26.7 vs. 8.2%; p = 0.025), fewer complete recanalization (45.2 vs. 71.0%; p = 0.028), and more persistent occlusions (37.5 vs. 10.6%; p = 0.011) on follow up MRA. There were no differences in reperfusion rates (83.9 vs. 84.0%; p = 0.986) nor in good long term functional outcome (50.0 vs. 51.1%; p = 0.921). Intracranial atherosclerosis etiology was more common in tapered than in non-tapered occlusions (54.8 vs. 18.0%; p < 0.001). Conclusion: The angiographic appearance of an occlusion in mechanical thrombectomy patients may determine its etiology, predict likelihood of successful recanalization, and risk of reocclusion.